2019
DOI: 10.1093/mnras/stz947
|View full text |Cite
|
Sign up to set email alerts
|

Ionization-driven intrinsic absorption line variability of BAL quasars in the Stripe 82 region

Abstract: We investigate the connection between the intrinsic C iv absorption line variability and the continuum flux changes of broad absorption line (BAL) quasars using a sample of 78 sources in the Stripe 82 region. The absorption trough variability parameters are measured using the archival multi-epoch spectroscopic data from the Sloan Digital Sky Survey (SDSS), and the continuum flux variability parameters are estimated from the photometric light curves obtained by the SDSS and the Catalina Real-Time Survey (CRTS) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 73 publications
(110 reference statements)
3
15
0
Order By: Relevance
“…Based on the statistical analysis of a sample of 2005 BAL quasars from the SDSS-I/II/III, He et al (2017) further concluded that variability of BAL in more than 80% of quasars are caused by the variation of the ionizing continuum. More recently, correlation between the variation of the ionizing continuum and BALs has been confirmed by several papers Vivek 2019). In the field of NALs, Lu et al (2017) confirmed, for the first time, the significant correlation between the variability of NALs and the ionizing continuum, using a twoepoch spectral sample of 40 quasars containing 52 variable C IVλλ1548, 1551 absorption doublets constructed by Chen et al (2015).…”
Section: Introductionmentioning
confidence: 84%
“…Based on the statistical analysis of a sample of 2005 BAL quasars from the SDSS-I/II/III, He et al (2017) further concluded that variability of BAL in more than 80% of quasars are caused by the variation of the ionizing continuum. More recently, correlation between the variation of the ionizing continuum and BALs has been confirmed by several papers Vivek 2019). In the field of NALs, Lu et al (2017) confirmed, for the first time, the significant correlation between the variability of NALs and the ionizing continuum, using a twoepoch spectral sample of 40 quasars containing 52 variable C IVλλ1548, 1551 absorption doublets constructed by Chen et al (2015).…”
Section: Introductionmentioning
confidence: 84%
“…Third, asynchronized variability has been identified between the continuum and absorption lines. Anticorrelations between the changes of the ionizing continuum and BALs have been proven (Lu et al 2018;Lu & Lin 2018c;Vivek 2019), which supports the IC scenario as the primary driver of the variability of broad absorption troughs. Therefore, the continuum variation can account for the variability in BAL to some extent.…”
Section: Variation Mechanismmentioning
confidence: 78%
“…Second, the continuum flux of the source shows obvious weakening. Correlations between the variations of the ionizing continuum and those of outflow absorption lines have already been proved (Lu et al 2017;Chen et al 2018a,b, 2019Lu et al 2018;Lu & Lin 2018c, 2019Huang et al 2019;Vivek 2019 for BALs), which could, at least to some extent, be served as an evidence for supporting the IC scenario as the main origin of absorption line variability. For J1208+0355, along with strengthenings of the absorption lines, the power-law continuum (the purple and blue smooth curves in Figure 1) in the second epoch is on average 41% lower than in the first epoch.…”
Section: Variation Mechanismmentioning
confidence: 89%